2013
DOI: 10.1186/scrt226
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of corneal stromal stem cells with the potential for epithelial transdifferentiation

Abstract: IntroductionThe corneal stroma is being increasingly recognized as a repository for stem cells. Like the limbal and endothelial niches, stromal stem cells often reside in the peripheral cornea and limbus. These peripheral and limbal corneal stromal cells (PLCSCs) are known to produce mesenchymal stem cells in vitro. Recently, a common corneal stromal and epithelial progenitor was hinted at. This study aims to examine the stem cell potential of corneal stromal cells and to investigate their epithelial transdiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 81 publications
3
59
0
4
Order By: Relevance
“…2F). Earlier studies, based on FACS analysis, reported CD29 as a marker of mesenchymal-like cells of the anterior limbal stroma [22,23,26]. However, we observed that the epithelial cells of individual holoclones specifically expressed CD29, and the colony periphery was lined by nestin-positive cells (Fig.…”
Section: Spatial Distribution Of Limbal Niche Cells In Vitromentioning
confidence: 46%
“…2F). Earlier studies, based on FACS analysis, reported CD29 as a marker of mesenchymal-like cells of the anterior limbal stroma [22,23,26]. However, we observed that the epithelial cells of individual holoclones specifically expressed CD29, and the colony periphery was lined by nestin-positive cells (Fig.…”
Section: Spatial Distribution Of Limbal Niche Cells In Vitromentioning
confidence: 46%
“…Human corneal stromal stem cells (CSSC) were isolated from corneal rims, using a modification of a previously described method [23]. Excess sclera was removed and the epithelium and endothelium detached by gentle scraping.…”
Section: Isolation and Culture Of Primary Human Corneal Stromal Stem mentioning
confidence: 99%
“…In vitro, keratocytes extracted from the limbus, have been shown to display characteristics of multipotent mesenchymal stromal cells (MSC) [20,22], that after several passages in a certain medium, conform to a criteria stipulated by the International Society for Cellular Therapy (ISCT) [18,23]. The extracted corneal stroma-derived stem cells (CSSC) express MSC-associated cell surface markers such as CD29, CD73, CD90 and CD105, and possess the ability to differentiate down the osteogenic, chondrogenic and adipogenic lineages in vitro [18,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include human mesenchymal stem cells [13], human embryonic stem cells [14], human corneal stroma stem cells [15,16], adipose-derived stem cells [17,18], and dental pulp stem cells [2].…”
Section: Introductionmentioning
confidence: 99%